Managerial Accounting, 7th Edition - Maryanne M. Mowen; Don R. Hansen; Dan L. Heitger (Cengage Learning, 2017)
Managerial accounting plays an essential role in helping today's managers make effective business decisions for their companies. Now MANAGERIAL ACCOUNTING, 7E shows you how. With a focus on "Here's How It's Used," this book makes managerial accounting meaningful, fun, and relevant to your life and business today. The book highlights exciting companies using relatable examples and scenarios throughout the book. You learn why managerial accounting is important, what it is, where managerial information comes from and how it is best used to make strong business decisions. You even explore emerging topics, such as sustainability, quality cost, lean accounting, international accounting, enterprise risk management, and forensic and fraud accounting. Accompanying videos and online materials help you understand and appreciate how managerial accounting is useful in both your professional and personal life.